Thermal and Physical Properties of Deccan Basalt and Neoarchean Basement Cores From a Deep Scientific Borehole in the Koyna−Warna Seismogenic Region, Deccan Volcanic Province, Western India: Implications on Thermal Modeling and Seismogenesis - Labani Ray; Ravindra Kumar Gupta; Nishu Chopra; Dhulipudi Gopinadh; Sujeet Kumar Dwivedi (Earth and Space Science, 2021)
Abstract We have investigated 78 core samples of basaltic trap and Neoarchean basement in the laboratory from a 981 m deep scientific borehole KBH‐05, in the Koyna−Warna seismic zone, in order to characterize their thermal and physical properties and present a probable crustal thermal model. The Koyna−Warna, located in the Deccan Volcanic Province (DVP), is globally one of the most prominent Reservoir Triggered Seismicity (RTS) regions. Thermal conductivity, density, and porosity vary widely (1.0–1.7 Wm−1K−1, 2,400–3,000 kg m−3, 0.2%–10%) for the basalt due to their lithological heterogeneities, i.e., massive/amygdaloidal/vesicular. In comparison, the basement, which dominantly consists of gneiss/migmatite gneiss (granodiorite to tonalite to quartz monzodiorite in composition) and amphibolite, have shown a wider range in thermal conductivity (2.2–3.4 Wm−1K−1) but constricted range in density and porosity (2,600–2,800 kg m−3, 0.01%–0.15%). Based on gamma and sonic logs, as well as radioelements (Th, U, K), the 499 m thick basaltic trap can be divided into two thick layers (325, 174 m) and five sub‐layers, which can be correlated with different basaltic formations. Similarly, the underlying basement can also be divided into two layers (93, 384 m). The upper basement layer has two times higher concentrations of Th and U than the lower layer, with heat production of 2.0, 0.8 μWm−3. Further, the study provides a robust temperature estimate of 165°C–250°C at 10 km depth, considerably higher than reported earlier for the DVP, and reveals that in addition to thermal parameters, RTS also plays an important role in the seismogenesis of the region.